Christopher L. Cahill. Issue 40 (25th September 2017) - Unknown
Abstract: "As an educator, I tend to get pretty excited about creating a forum in which people can excel and do their best work…" Find out more about this author's research athttps://doi.org/10.1002/ejic.201700788 . Abstract : "As an educator, I tend to get pretty excited about creating a forum in which people can excel and do their best work…" Find out more about this author's research athttps://doi.org/10.1002/ejic.201700788 .